High-Fidelity Reprogrammed Human IPSCs Have a High Efficacy of DNA Repair and Resemble hESCs in Their MYC Transcriptional Signature - Pratik K. Nagaria; Carine Robert; Tea Soon Park; Jeffrey S. Huo; Elias T. Zambidis; Feyruz V. Rassool (Hindawi Limited, 2016)
Human induced pluripotent stem cells (hiPSCs) are reprogrammed from adult or progenitor somatic cells and must make substantial adaptations to ensure genomic stability in order to become "embryonic stem cell- (ESC-) like." The DNA damage response (DDR) is critical for maintenance of such genomic integrity. Herein, we determined whether cell of origin and reprogramming method influence the DDR of hiPSCs. We demonstrate that hiPSCs derived from cord blood (CB) myeloid progenitors (i.e., CB-iPSC) via an efficient high-fidelity stromal-activated (sa) method closely resembled hESCs in DNA repair gene expression signature and irradiation-induced DDR, relative to hiPSCs generated from CB or fibroblasts via standard methods. Furthermore, sa-CB-iPSCs also more closely resembled hESCs in accuracy of nonhomologous end joining (NHEJ), DNA double-strand break (DSB) repair, and C-MYC transcriptional signatures, relative to standard hiPSCs. Our data suggests that hiPSCs derived via more efficient reprogramming methods possess more hESC-like activated MYC signatures and DDR signaling. Thus, an authentic MYC molecular signature may serve as an important biomarker in characterizing the genomic integrity in hiPSCs.